Extended topology based recommendation system for unidirectional social networks. Issue 7 (1st May 2015) - Yigit, Melike; Bilgin, Bilal E.; Karahoca, Adem
Highlights Proposed approach (PA) has extension to the topology based recommendation system. PA extended RSs is tested and validated by computing an original score formula. The benchmarking study results show that PA has advantages.